2005
DOI: 10.1002/ceat.200500054
|View full text |Cite
|
Sign up to set email alerts
|

Fluidization Behaviors for Coating Cohesive Particles

Abstract: Communications the feed streams. The inner diameter was 1600 lm. At position 12 a tantalum orifice plate with nine orifices, each 100 lm, was installed. The sulfuric acid was injected here. At position 13 the main components were mixed. At position 14 a tantalum orifice plate with one orifice, 35 lm, was installed. The nitric acid was injected at this point. At position 16 a tantalum orifice plate with one orifice, 35 lm, was installed, and the benzene was injected at this position. At position 15 a tantalum o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The optimum frequency values for sawdust and wheat stalk were 150 and 200 Hz, respectively. For Geldart C/A particles, other researchers found that there was a minimum value in the curve of minimum fluidization velocity versus sound frequency. Their conclusion for Geldart C/A particles is similar to the results obtained for biomass particles in this work.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The optimum frequency values for sawdust and wheat stalk were 150 and 200 Hz, respectively. For Geldart C/A particles, other researchers found that there was a minimum value in the curve of minimum fluidization velocity versus sound frequency. Their conclusion for Geldart C/A particles is similar to the results obtained for biomass particles in this work.…”
Section: Resultsmentioning
confidence: 95%
“…Zhu et al found that, for a given sound pressure level and bed weight, the minimum fluidization velocity was significantly reduced and elutriation of nanoparticles agglomerates was much weakened. An acoustic fluidized bed with nanoparticles as the bed material was employed by Guo et al, who found that increasing sound pressure levels result in a decrease in minimum fluidization velocity and an increase in bubble frequency. In addition, Xu et al reported the influence of sound waves on fluidization of fluid catalytic cracking particles.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated [1,2] that ultrafine particle fluidization is a promising technology for a number of applications of ultrafine particles. Up to now, ultrafine particles have been fluidized, forming agglomerates at the superficial gas velocity, exceeding the minimum fluidization velocity of primary particles.…”
Section: Introductionmentioning
confidence: 99%
“…As the superficial gas velocity u is increased from 0.0237±0.0775 m/s, stable channels are formed in the static bed which is charaterized by a low pressure drop 1) . Because of channeling and cracking, the fluidization behaviors of the bed are very unstable, indicating that no reproducible results are obtained by repetition of the experiment [9].…”
Section: Fluidization Behaviors Of 30 Nm Tio 2 Particlesmentioning
confidence: 97%